Effects of Commercial Probiotics on Sperm Traits, Intestinal Morphology, Gut Microflora, and Antioxidant Status in 65-Week-Old Ross 308 Broiler Breeder Roosters - Arash Hadavi; Farogh Kargar; Najeebullah Fayaz; Ali Tayebi pour; Muhammad Namazi zadgan (پژوهشهای علوم دامی ایران)
Introduction: Probiotics are live microbial feed supplements that exert beneficial effects on host animals by enhancing the balance of intestinal microbes (Fesseha, 2019). In poultry production, probiotics are increasingly viewed as alternatives to oral antibiotics due to growing concerns regarding antimicrobial resistance (Ogbuewu et al., 2022). Bacillus probiotics, in particular, have shown significant promise thanks to their spore-forming capabilities and resistance to feed processing (Ogbuewu et al., 2022). The stability of Bacillus spores in various stressful conditions, along with their ability to produce a range of enzymes such as protease, amylase, and lipase, makes them suitable food additives (Lei et al., 2013). Research indicates that probiotic supplementation can enhance growth performance, feed conversion efficiency, and antioxidant status in broilers (Jadhav et al., 2015; Ogbuewu et al., 2022). Additionally, probiotics contribute to improved intestinal health by promoting beneficial microflora and enhancing intestinal morphology (Ogbuewu et al., 2022). Likewise, probiotics can boost various performance and health parameters in poultry, including body weight gain, feed conversion ratio, and overall intestinal health (Alhefny et al., 2022; Aziz et al., 2022; Hassan et al.,2023; Prentza et al., 2022; Smolovskaya et al., 2023).The administration of synbiotics has been associated with positive effects on gut health, survival rates, and the composition of gut microbiota in broiler hens, suggesting potential benefits for reproductive performance and overall health in later life (Prentza et al., 2022). Furthermore, the use of probiotics does not lead to antibiotic resistance in intestinal bacteria, nor does it cause the accumulation of antibiotics in bird tissues (Angelakis, 2017; Blajman et al., 2015). Common probiotic strains utilized in poultry include species of Lactobacillus, Enterococcus, and Bacillus (Fesseha, 2019). Although probiotics demonstrate potential as growth promoters, their effects can vary depending on the specific strains used and their dosages (Ahmad,2006). The characteristics of an effective probiotic include the following:1. It is non-pathogenic.2. It exerts a positive effect on the host animal.3. It can survive in the intestinal environment.4. It remains viable under storage conditions.5. It has a high shelf life during processing.6. It competes effectively with harmful bacteria (Smirnov et al., 2005).Materials and Methods: This experiment aimed to investigate the effects of commercial probiotics on sperm traits, intestinal morphology, gut microflora, and antioxidant status in 65-week-old Ross 308 male broiler breeders. A completely randomized design was used with 5 treatments, 10 replications, and one male per unit, totaling 50 males. Sperm characteristics were assessed by collecting samples using the abdominal rub method every ten days. The eosin and nigrosine staining method determined the percentage of live and dead sperm. Antioxidant capacity and glutathione peroxidase activity were also measured. At the experiment's conclusion, all roosters were slaughtered to evaluate intestinal morphology and quantify E. coli and Lactobacillus populations.Results and Discussion: The effects of varying levels of commercial probiotics on sperm parameters—such as volume, motility, live sperm percentage, sperm count, and abnormal sperm percentage—in 65-week-old Ross 308 broiler breeders are detailed in Table 3. The study found that the experimental treatments did not significantly affect sperm volume, motility, or live sperm percentage. However, during the first and second months, sperm counts in groups receiving 100, 150, and 200 mg/kg of probiotics were significantly higher than in the control group (P<0.05). Bacillus supplementation notably increased live sperm counts (Mazanko et al., 2018). Additionally, the percentage of abnormal sperm was significantly lower (P<0.01) in the 100, 150, and 200 mg/kg probiotic groups compared to controls. Consistent with our findings, vitamin E has been reported to enhance semen volume, sperm motility, and egg fertility, while vitamin C reduces dead sperm percentages (Khan et al., 2012; Khan et al., 2013). In the first month, supplementation with 150 and 200 mg/kg of probiotics, and in the second month with 50, 150, and 200 mg/kg, significantly increased total antioxidant capacity (P<0.05). Probiotics also significantly increased villi length, with the highest jejunum villi length observed in the 150 mg/kg group (1231 micrometers) compared to the control (1156 micrometers). The villus-to-crypt depth ratio was highest in the 150 mg/kg group, showing significant improvement over controls. Probiotic addition significantly increased Lactobacillus numbers in the jejunum and ileum (P<0.05), while E. coli counts in the jejunum were significantly reduced compared to the control group.Conclusion: The study demonstrated that probiotics in poultry nutrition enhance the immune system by settling in the digestive tract, preventing pathogens from adhering to intestinal villi, creating acidic conditions, and producing bactericides. This, in turn, improves nutrient digestion. Additionally, roosters fed with 100, 150, and 200 mg/kg probiotics showed a significantly higher number of live sperm compared to the control group. Overall, based on sperm characteristics, intestinal morphology, gut microflora, and antioxidant status, 100 mg/kg of probiotics is recommended as the optimal dosage.